Removal Of Copper (II) And Nickel (II) In Aqueous Solution By Modified Rhizophora Apiculata Barks Adsorbent - Amat, Rozaini Che (2012)
Waste mangrove barks of Rhizophora apiculata has been chemically modified in different conditions to be used as adsorbents to remove Cu(II) and Ni(II) ions from aqueous solution. Rhizophora apiculata bark mainly consists of 53% cellulose, 48% lignin, 46% extractive and 13% ash content.Chemical modifications were done using formaldehyde as cross linking agent in acidic and basic conditions. The adsorbents were chemically and physically characterised by FTIR spectroscopy, pHzpc and BET analysis shows that the adsorbent produced are insoluble in water and have micro porous texture.